Penis Transplantation: First US Experience. Issue 5 (May 2018) - Cetrulo, Curtis L.; Li, Kai; Salinas, Harry M.; Treiser, Matthew D.; Schol, Ilse; Barrisford, Glen W.; McGovern, Francis J.; Feldman, Adam S.; Grant, Michael T.; Tanrikut, Cigdem; Lee, Jeffrey H.; Ehrlichman, Richard J.; et al.
Abstract : Objective: We describe the first successful penis transplant in the United States in a patient with a history of subtotal penectomy for penile cancer. Background: Penis transplantation represents a new paradigm in restoring anatomic appearance, urine conduit, and sexual function after genitourinary tissue loss. To date, only 2 penis transplants have been performed worldwide. Methods: After institutional review board approval, extensive medical, surgical, and radiological evaluations of the patient were performed. His candidacy was reviewed by a multidisciplinary team of surgeons, physicians, psychiatrists, social workers, and nurse coordinators. After appropriate donor identification and recipient induction with antithymocyte globulin, allograft procurement and recipient preparation took place concurrently. Anastomoses of the urethra, corpora, cavernosal and dorsal arteries, dorsal vein, and dorsal nerves were performed, and also inclusion of a donor skin pedicle as the composite allograft. Maintenance immunosuppression consisted of mycophenolate mofetil, tacrolimus, and methylprednisolone. Results: Intraoperative, the allograft had excellent capillary refill and strong Doppler signals after revascularization. Operative reinterventions on postoperative days (PODs) 2 and 13 were required for hematoma evacuation and skin eschar debridement. At 3 weeks, no anastomotic leaks were detected on urethrogram, and the catheter was removed. Steroid resistant-rejection developed on POD 28 (Banff I), progressed by POD 32 (Banff III), and required a repeat course of methylprednisolone and antithymocyte globulin. At 7 months, the patient has recovered partial sensation of the penile shaft and has spontaneous penile tumescence. Our patient reports increased overall health satisfaction, dramatic improvement of self-image, and optimism for the future. Conclusions: We have shown that it is feasible to perform penile transplantation with excellent results. Furthermore, this experience demonstrates that penile transplantation can be successfully performed with conventional immunosuppression. We propose that our successful penile transplantation pilot experience represents a proof of concept for an evolution in reconstructive transplantation. Abstract : Supplemental Digital Content is available in the text